Impact of Micro-finance on Educational Change of Women - Acharya, Gyanu (Education and Development, 2020)
Women cooperatives have been established to provide the poor women with the financial support in order to transform their socio-economic status. The present study has attempted to find out the educational changes among the client women in the study area after the intervention of women cooperatives. This study had adopted descriptive and analytical research design and mixed method – whereby the client women of Women Cooperative SocietyLimited, Thankot Branch were taken as population and 62 of them were sampled for data were collection. The primary data were collected through a set of questionnaires, and for secondary data, different documents of WCS’s central branch and Thankot branch, Central Bureau of Statistics, Ministry, research reports, relevant books and journals were consulted. From the study it was found that socio-economic status of poor women was changed through WCS micro-finance programme. The result also showed that saving and income were increased to 17.74 percent and 10.72 respectively. Education and literacy level of households are changed by 35% and 8% respectively.